NONLOCAL EFFECTS IN THE NUCLEUS-NUCLEUS FUSION CROSS-SECTION - Galetti, D.; Ribeiro, MAC (American Physical Soc, 1994)
Effects of the nonlocality of factorizable potentials are taken into account in the calculation of nucleus-nucleus fusion cross section through an effective mass approach. This cross section makes use of the tunneling factor calculated for the nonlocal barrier, without the explicit introduction of any result coming from coupled channel calculation, besides the approximations of Hill-Wheeler and Wong. Its new expression embodies the nonlocal effects in a factor which redefines the local potential barrier curvature. Applications to different systems, namely O-16 + Co-59, O-16,O-18 + Ni-58,Ni-60,Ni-64, and O-16,O-18 + Cu-63,Cu-65 are presented, where the nonlocal range is treated as a free parameter.